A Flat-Lensed Spiral Phase Plate Based on Phase-Shifting Surface for Generation of Millimeter-Wave OAM Beam - Chen, Yiling; Zheng, Shilie; Li, Yue; Hui, Xiaonan; Jin, Xiaofeng; Chi, Hao; Zhang, Xianmin (IEEE antennas and wireless propagation letters, 2016)
A multilayer phase-shifting-surface-based flat plate is designed to offer a combination of lens and spiral phase plate (SPP) for orbital angular momentum (OAM) beam generation and convergence at 60 GHz. The proposed design consists of a series of phase-shift unit cells to control the emergent phase and form a flat lens for the purpose of beam focusing. The results of simulation and experiment verify that the OAM beam with small divergence angle can be achieved.